2000
DOI: 10.1007/s001340000710
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sepsis-related Organ Failure Assessment (SOFA) score and CIS (cellular injury score) for scoring of severity for patients with multiple organ dysfunction syndrome (MODS)

Abstract: Both SOFA score and CIS sequentially reflected the severity of MODS. Furthermore, they were comparable in diagnostic value as predictors of prognosis. These findings may indicate the possibility that MODS is a summation of effects of cellular injury. In addition, sequential evaluation of both SOFA score and CIS would provide a more accurate prediction of prognosis than conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…The infections were determined to be communityacquired pneumonia, acute pyelonephritis, acute intraabdominal infection, and primary bacteremia. The degree of sepsis was evaluated by using the SOFA score [15]. Additional information is available in the Electronic Supplementary Material (ESM) [16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…The infections were determined to be communityacquired pneumonia, acute pyelonephritis, acute intraabdominal infection, and primary bacteremia. The degree of sepsis was evaluated by using the SOFA score [15]. Additional information is available in the Electronic Supplementary Material (ESM) [16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…This state is called systemic inflammatory response syndrome (1,2). The incidence of sepsis is extremely high in the intensive care unit (ICU), with a mortality of ≤40-80%.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that there are significant differenc es in the value of the SOFA and ElebuteStoner score for differentiation of mor tality or MODS. Oda et al [31] had sim ilar cutoff values at admission with ours, with a higher sensitivity and specificity (71.3 and 76.9%, respectively); however, they focused on MODS. Another study by Moreno et al [30] that included 1,449 interdisciplinary ICU patients, found an AUC of 0.847 and 0.772 for the for the maximum SOFA score on admission.…”
Section: Scoring In Cardiogenic Shockmentioning
confidence: 48%